Detection of African swine fever, classical swine fever, and foot-and-mouth disease viruses in swine oral fluids by multiplex reverse transcription real-time polymerase chain reaction. (March 2015) - Grau, Frederic R.; Schroeder, Megan E.; Mulhern, Erin L.; McIntosh, Michael T.; Bounpheng, Mangkey A.
African swine fever (ASF), classical swine fever (CSF), and foot-and-mouth disease (FMD) are highly contagious animal diseases of significant economic importance. Pigs infected with ASF and CSF viruses (ASFV and CSFV) develop clinical signs that may be indistinguishable from other diseases. Likewise, various causes of vesicular disease can mimic clinical signs caused by the FMD virus (FMDV). Early detection is critical to limiting the impact and spread of these disease outbreaks, and the ability to perform herd-level surveillance for all 3 diseases rapidly and cost effectively using a single diagnostic sample and test is highly desirable. This study assessed the feasibility of simultaneous ASFV, CSFV, and FMDV detection by multiplex reverse transcription real-time polymerase chain reaction (mRT-qPCR) in swine oral fluids collected through the use of chewing ropes. Animal groups were experimentally infected independently with each virus, observed for clinical signs, and oral fluids collected and tested throughout the course of infection. All animal groups chewed on the ropes readily before and after onset of clinical signs and before onset of lameness or serious clinical signs. ASFV was detected as early as 3 days postinoculation (dpi), 2–3 days before onset of clinical disease; CSFV was detected at 5 dpi, coincident with onset of clinical disease; and FMDV was detected as early as 1 dpi, 1 day before the onset of clinical disease. Equivalent results were observed in 4 independent studies and demonstrate the feasibility of oral fluids and mRT-qPCR for surveillance of ASF, CSF, and FMD in swine populations.